Waste Water Treatment and Reutilization - Sebastián García Einschlag, Fernando (IntechOpen, 2011)
The steady increase in industrialization, urbanization and enormous population growth are leading to production of huge quantities of wastewaters that may frequently cause environmental hazards. This makes waste water treatment and waste water reduction very important issues. The book offers a collection of studies and findings concerning waste water treatment, minimization and reuse.